Associations of circulating adipokines and coronary artery disease in young adults - A. D. Khudiakova; Y. V. Polonskaya; L. V. Shcherbakova; V. S. Shramko; N. A. Kuzminykh; E. V. Kashtanova; Yu. I. Ragino (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the associations of abdominal obesity (AO), adipokines and premature coronary artery disease (CAD) in young people for a deeper understanding of the pathogenesis of atherosclerotic diseases.Material and methods. A total of 1457 people were examined, including 653 (44,8%) men. Mean age was 36,7±6,0 years. Premature CAD was detected in 46 people, while 4 following subgroups were formed (138 people in total): with CAD and AO; with CAD, without AO; control groups by age and sex: without CAD, with AO; without CAD, without AO.Results. Premature CAD in young people is associated with an increase in non-high-density lipoprotein cholesterol (non-HDL-C). Univariate analysis found that the probability of CAD increased by 1% with an increase in adiponectin level, and by 0,2% with an increase of 1 ng/ml in resistin level. Multivariate regression analysis, including sex, age, waist circumference, non-HD-C, adiponectin, and resistin, significant associations were obtained for non-HDL-C and adiponectin. With AO, the CAD probability increased by 0,6% with an increase in plasminogen activator inhibitor-1 level (PAI-1). However, when non-HDL-C was included in the model, significance for this biomarker was not achieved.Conclusion. In young people, CAD is associated with increased levels of non-HDL cholesterol, adiponectin, resistin and PAI-1. Independent associations with premature CAD were obtained only for adiponectin, which makes this marker promising for study in young people.